The effect of coarse aggregate’s physical properties on the performance of porous asphalt mixture (PAM) - Lim, Derrick Teck Swee (2019)
The Jurong Rock Cavern project has resulted in the excavation of nearly 4 million m³ of sedimentary rocks. However, Singapore is a small country with limited landfill space and this causes foreseeable storage issues in the near future. Hence, it is necessary to find a beneficial and suitable purpose for the rocks. The objective of this project is to investigate the plausibility of using the sedimentary rocks to construct pavements made of porous asphalt mixture and finding out how different physical properties of the sedimentary rock aggregates affect the performance of the porous asphalt mixture. Granite aggregates were used in the first stage of the study to determine the optimal gradation. They were categorised into five groups; namely G1, G2, G3, G4 and G5, each of which consisted of a different gradation. The granite aggregates were mixed with PG 76 binder and hydrated lime fillers and cast using a gyration machine. The specimens which were cast were then evaluated through four tests: Marshall Stability test, Permeability test, Cantabro Abrasion test, and Draindown test. The results were then consolidated, analysed and compared to determine the optimal gradation to be used for the next stage of the study. Jurong sedimentary rocks were used for the second stage of the study. The different shapes of rocks used were blade, cubical and disk. The gradation of the specimens was based on the results from the first test. The specimens cast were put through the four aforementioned tests and the Dynamic Creep test, and the results evaluated to determine which aggregate shape produced the porous asphalt mixture with the best performance. Based on the results obtained, the cubical design blend produced the most promising results with its high strength, durability and permeability. However, more research can be done to further improve the quality of the design.